1990
DOI: 10.1097/00006123-199001000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy

Abstract: Long-term extracranial shunting for hydrocephalus has numerous drawbacks related to shunt malfunction and infection. In some cases outcome has been very disappointing. We successfully managed 5 patients with acquired aqueductal stenoses with no significant morbidity by the use of an intracranial cerebrospinal fluid diversion, namely a third ventriculostomy. First advocated by Dandy, ventriculostomy was largely passed over in favor of extracranial procedures. With improved surgical techniques, however, ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(57 citation statements)
references
References 0 publications
0
56
1
Order By: Relevance
“…(2) High failure rates of ETV in children have been reported by some authors. Jones et al [23] performed ETV in 5 patients aged less than 1 year with a success rate of 60%. Hopf et al [10] reported 4 cases in neonates which all failed.…”
Section: Discussionmentioning
confidence: 99%
“…(2) High failure rates of ETV in children have been reported by some authors. Jones et al [23] performed ETV in 5 patients aged less than 1 year with a success rate of 60%. Hopf et al [10] reported 4 cases in neonates which all failed.…”
Section: Discussionmentioning
confidence: 99%
“…ETV has been reported to be effective in the treatment of hydrocephalus with success rates ranging between 49 and 100%, depending on the aetiology of hydrocephalus, the criteria used for patient selection, and the follow-up period [2, 3, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. Despite these encouraging reports, most authors have suggested that the outcome following ETV is significantly worse in children less than 1 year old as compared with older children [4, 10, 16, 17, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Initially reported to work best in patients with late-onset aqueduct stenosis (AS), endoscopic third ventriculostomy (ETV) is now used in many centres for a wider variety of indications with varying success rates, depending on the aetiology of the hydrocephalus and the patient’s age [1, 2, 3, 4]. Despite the excellent results achieved in adults and older children, the reported outcome of ETV in children less than 1 year old has been disappointing, with success rates ranging between 0 and 23% [2, 5].…”
Section: Introductionmentioning
confidence: 99%
“…If an increase in valve pressure causes neurological symptoms for patients with a history of overdrainage, adding a TV should be considered in those with obstructive hydrocephalus as an adjunct to facilitate increasing the pressure. Other advantages of maintaining an internal CSF pathway include improvement in brain compliance [12]and maintaining absorption ability, which may help reduce the symptoms of a malfunctioning shunt system [13]. …”
Section: Discussionmentioning
confidence: 99%